Federico Gerdes on the 150th anniversary of his birth and the 70th anniversary of his death: An overview - Tello Malpartida, Aurelio (2023)
Federico Gerdes has been considered a musician with an important presence in the history of Peruvian music. Several reasons support this: he was the founding director of the first house of academic studies in Peru and directed it for thirty-five years; he carried out the musical life of Peru’s capital city for more than four decades; he introduced an unknown repertoire in our country that opened the aesthetic horizons and shaped the taste of music lovers. He composed a handful of rigorously crafted works that, despite their brevity and limited breadth, contain high musical values. He extended his romantic vision of music, in which he had trained until his last days. Living at the same time of both nationalisms and indigenism trends, he remained oblivious to those concerns. He laid strong bases for a musical culture whose significance remains in our time. In commemoration of the sesquicentennial of his birth and the seventieth anniversary of his death, hereby is a brief review of his character, his work, his actions, and the imprint he left on our music.